Phormidium ambiguum Gomont 1892 - Gupta, Pratibha (Zenodo, 2021)
Phormidium ambiguum Gomont Annales des Sciences Naturelles, Botanique, Série 7 (16): 178 (Gomont 1892). Desikachary, Cyanophyta 266, t. 44, f. 16 (Desikachary 1959). Komárek & Anagn., Cyanoprokaryota Part 2: Oscillatoriales 19 (2): 479 (Komárek & Anagnostidis 2005). DESCRIPTION. — Filament elongate; sheath thin, firm, mucilaginous, colourless, sometime thicker diffluent, sometimes more or less lamellated; trichome slightly constricted or sometimes not constricted at the cross-walls; end not attenuated, not capitate, blue-green; cells not granulated at the cross-walls or sometimes granulated; end cell rounded, calyptra absent (Fig. 8I). DIMENSION. — Trichome 3.5-7. 8 µm broad and cells 1.2-3.4 µm long. ENVIRONMENT & HABITAT. — Freshwater and marine species; wet rocks, free-floating & benthic in stagnant water; temperature 3.5°C. Published as part of Gupta, Pratibha, 2021, First report of diversity of Cyanobacteria of Broknes Peninsula of Larsemann Hills, East Antarctica, pp. 241-251 in Cryptogamie, Algologie 20 (15) on page 247, DOI:10.5252/cryptogamie-algologie2021v42a15, http://zenodo.org/record/7819309